ANALISIS KESALAHAN SISWA KELAS X DI SMA N 1 LEMBAH MELINTANG DALAM MENYELESAIKAN SOAL BARISAN DAN DERET MENURUT TEORI NEWMAN - Atsari Fitria; Iltavia Iltavia; Nurul Hikmi (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
In the world of education, mathematics is often considered the subject most feared and avoided by students, this happens because mathematics is abstract in nature so students have difficulty understanding the problems in mathematics. Apart from that, mathematics is considered difficult because it is related to numbers and formulas. This research was carried out in conjunction with field practice (PL) activities. In the PL activities carried out by researchers for approximately 4 months, researchers found many problems when teaching, one of which was students' mistakes in solving sequence and series questions. The aim of this research is to determine the level of students' understanding and difficulty with sequence and series material, so that it can be used as knowledge for teachers to improve the quality of learning in the future. This research is a qualitative descriptive study to examine the errors made by students in solving questions about sequences and series. The subjects of this research were 23 class X students of SMAN 1 Lembah Melintang. The error analysis used in this research uses the error analysis stages according to Newman. By conducting this research, students' level of understanding and difficulty in sequences and series.